(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Cancer remains one of the leading causes of morbidity and mortality worldwide. The development of malignant neoplasms results from complex interactions among environmental carcinogens, genetic susceptibility, epigenetic alterations, and dysregulated cellular signaling pathways.